A NORMAL CRITERION CONCERNING SEQUENCE OF FUNCTIONS AND THEIR DIFFERENTIAL POLYNOMIALS - N. Bharti (Проблемы анализа)
In this paper, we study normality of a sequence of meromorphic functions whose differential polynomials satisfy a certain condition. We also give examples to show that the result is sharp.